Bilateral Conjunctival Infiltration as an Extramedullary Relapse of AML - Mozaheb, Zahra (Case Rep Hematol, 2018)
Acute myelogenous leukemia (AML) accounts for 1.2% of all cancer deaths. Relapse is the major cause of treatment failure in acute myeloid leukemia (AML) patients. AML rarely presents as ocular manifestation in relapse or at presentation. The M4 subtype of AML is most commonly presented with extramedullary involvement. In this report, we presented a young female with AML who was diagnosed and treated for AML about 40 months ago. She did not transplant because she did not have a full-match donor. About 4 months ago, she visited with a red eye and conjunctival infiltration. She was referred to an ophthalmologist for a biopsy, and the pathology report showed the relapse of AML which was treated with systemic chemotherapy. Red eyes with subconjunctival nodules in patients with a history of previous AML should raise the suspicion for recurrent disease that warrants urgent biopsy and systemic treatment. Eye involvement with leukemia is usually responsive to systemic chemotherapy.